From the slit-island method to the Ising model: Analysis of irregular grayscale objects - Mazurek, Przemysław; Oszutowska-Mazurek, Dorota (Zielona Góra: Uniwersytet Zielonogórski)
The Slit Island Method (SIM) is a technique for the estimation of the fractal dimension of an object by determining the area- perimeter relations for successive slits. The SIM could be applied for image analysis of irregular grayscale objects and their classification using the fractal dimension. It is known that this technique is not functional in some cases.
Keywords: slit island method; area-perimeter method; Ising model; image analysis; cervical cancer